Strategies for Developing Student Capability in Anticipating The Impact of Globalization - Sefenrius Buulolo; Agusnita Zebua; Rita Sujud Yanti Lase (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research contains the development of students' abilities in anticipating the impact of globalization with the aim of improving the use of blogs, vlogs and multimedia presentations as research instruments to provide rich and varied insights into students' abilities. This learning process only focuses on developing students' abilities in anticipating the impact of globalization, which is useful for improving their use of developing the impact of globalization, including blogs, vlogs and multimedia presentations so that learning objectives can be achieved. The method used in this research is qualitative research with the approach used is a descriptive approach. The data collection techniques used in this research are tests, observations, interviews, interviews. It can be concluded that the strategy is to develop students' abilities in anticipating the impact of globalization.